On Some Euler Sequence Spaces of Nonabsolute Type - Altay, B.; Başar, F. (Український математичний журнал, 2005)
In the present paper, the Euler sequence spaces eʳ₀ and eʳc of nonabsolute type which are the BK-spaces including the spaces c₀ and c have been introduced and proved that the spaces er₀ and erᶜ are linearly i somorphic to the spaces c₀ and c, respectively. Furthemore, some inclusion theorems have been given. Additionally, the α−,β−,γ− and continuous duals of the spaces eʳ₀ and eʳc have been computed and their basis have been constructed. Finally, the necessary and sufficient conditions on an infinite matrix belonging to the classes (eʳc : lp) and (eʳc : c) have been determined and the characterizations of some other classes of infinite matrices have also been derived by means of a given basic lemma, where 1 ≤ p ≤ ∞. Введено поняття просторів послідовностей Ейлера eʳ₀ та eʳc неабсолютного типу — BK-просторів, що містять простори c₀ та c. Доведено, що простори eʳ₀ та eʳc лінійно ізоморфні відповідно до просторів c₀ та c. Наведено деякі теореми про включення. Крім того, обчислено α−,β−,γ− та неперервні простори, дуальні до просторів eʳ₀ та erc, і побудовано базиси цих просторів. Визначено необхідні та достатні умови належності нескінченної матриці до класів (eʳc : lp) та (eʳc : c). Отримано характеристики деяких інших класів нескінченних матриць з використанням наведеної в роботі основної леми для випадку 1 ≤ p ≤ ∞.